Determining Electron Transfer Kinetics at Porous Electrodes. (10th February 2017) - Friedl, Jochen; Stimming, Ulrich
Abstract: Porous carbon materials are of tremendous importance for electrochemical energy storage. Their low cost, wide potential window and high surface area make them ideal electrodes for many applications. The activity of the electrode towards a certain reaction is given by both the available wetted surface area and the electron transfer constant k0 . The present study investigates which electrochemical methods are suitable to determine k0 on porous carbon electrodes. For this purpose, we investigate the ferric/ferrous redox couple on a porous carbon nanotube electrode as model system. We show that results from cyclic voltammetry (CV) can yield an apparent catalytic effect and elucidate its origin. Chronoamperometry and electrochemical impedance spectroscopy are shown to produce consistent values for the exchange current density I0, which can then be normalized to k0 . Limitations of both methods in terms of k0 and diffusion constants are discussed. The gathered insights in terms of validity of methods on porous electrodes are harnessed to review the recent literature on the vanadium redox reactions. Reported k0 values spread over four orders of magnitude and there is no consensus on the influence of heat- or acid-treatment on the kinetics. Taking into account the difficulties of CVs on porous electrodes we conclude that reasonable values for the vanadium reactions are k 0 < 1.2 10 − 4 c m s − 1 and that oxidation of the samples increases surface area, catalyzes the V 2+ /V 3+ redox reaction but impedes the VO 2+ /VO2 + redox reaction.